A novel hybrid evaluation approach of knowledge management performance for R&D division. (1st January 2012) - Huang, Mu-Jung; Chen, Mu-Yen; Lee, Tai-Chun
After a series of strategies in knowledge management was executed, there must be a metric mechanism which is used to understand the results of knowledge management efficiency and effect. The role of R&D division is to benefit the corporate growth, the long-term innovation and the future competitive advantage. Thus, if R&D division in enterprise would be able to incorporate with knowledge management, it can reduce the variables of uncertainties within new product and obtain the higher probabilities for success. In this research, we integrated data envelope analysis (DEA) and analytic hierarchy process (AHP) approaches to measure knowledge management performance for R&D division and to conduct efficiency analysis of the quality and enterprise performance. We proposed the process of knowledge management and new product development achieving the goal of enterprises. Therefore, the R&D division in enterprises could make the improvement strategy activity.